Transformationes in the legal doctrine: pluralism of the methodologies, concept of the legal intercourse, legal hermeneutics - Гетьман, І. В. (Problems of legality, 2014)
The article examines the current transformation in the domestic legal doctrine. In particular received detailing the specific features of the information society, emerging in Ukraine, the interrelation between social trends and changes in the legal doctrine in the first place, is its methodological component. Provided brief description of popular methodologies in modern conditions of law, than when attention is focused on the concept of «legal intercourse», as modified in the domestic legal foundation communicative methodology of understanding law. The research of the process of adaptation of Ukrainian legislation, using the applied knowledge of the theory of understanding − hermeneutics, in particular its legal component. The paper received the detail design of the adaptation process as a mental activity, withdrawn its stages, studied the prerequisites set forth alternative knowledge on this subject.